Digital Transformation in Portuguese internationalized enterprises [abstract] - Santos-Pereira, Carla (2022)
The reality of Portuguese SMEs regarding internationalization has evolved at an accelerated pace due to the digital transformation imposed, in recent years, by the conditions determined by COVID-19. [...]